×Ellipisorus nom. nov. for ×Lepinema (Polypodiaceae) and ×Ellipisorus inaequibasis com. nov. from China - Zhang, Liang; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2020)
A new generic name, ×Ellipisorus, is proposed to replace ×Lepinema, a hybrid fern genus between Ellipinema and Lepisorus (Polypodiaceae).